ELECTROCATALYTIC ACTIVITY OF BAMBOO-LIKE MULTI WALLED CARBON NANOTUBES FOR THE DETERMINATION OF ASCORBIC ACID - V. MOHANA KRISHNA; T. SOMANATHAN (International Journal of Pharma and Bio Sciences, 2015)
Bamboo-like multi walled carbon nanotubes (b-CNTs) were synthesized by chemical vapour deposition technique (CVD) using copper supported catalyst and the obtained product were purified by a simple acid treatment. Purified CNTs were characterized by FE-SEM and HR-TEM analysis, which clearly reveals the formation of multi layers of graphitic carbon tubular structures and having diameter between 4 – 10 nm, respectively. The purified CNTs were used for the modification of carbon paste electrode (CPE) to determine ascorbic acid (AA) by using cyclic voltammetry (CV) technique. The modified electrode exhibited a rapid response to AA within 5s and showed a linear correlation to AA concentration in a range from 10×10-6 to 50×10-6 M. Stability of the modified electrode was also evaluated by repeating the experiment for 20 days and results show good stability. From this study, we confer that without using redox mediator, CNTs with carbon paste will results in good electrocatalytic activity towards oxidation of AA.